2013
DOI: 10.1038/nrneurol.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Susac syndrome: a review of all reported cases

Abstract: In Susac syndrome, occlusions of microvessels--presumed to be mediated by an autoimmune response to an as yet unknown antigen--lead to a characteristic clinical triad of CNS dysfunction, branch retinal artery occlusions, and sensorineural hearing impairment. Susac syndrome is considered a rare but important differential diagnosis in numerous neurological, psychiatric, ophthalmological, and ear, nose and throat disorders. Improved understanding of this disorder is crucial, therefore, to ensure that patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
372
5
58

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(453 citation statements)
references
References 129 publications
18
372
5
58
Order By: Relevance
“…Unlike our case, the clinical triad occurs at disease onset in only a minority of patients. In fact, the largest meta-analysis published by Dorr et al found that only 13% of patients show the clinical triad at disease onset (4). That is why SS may be underdiagnosed.…”
Section: N Case Reportmentioning
confidence: 99%
“…Unlike our case, the clinical triad occurs at disease onset in only a minority of patients. In fact, the largest meta-analysis published by Dorr et al found that only 13% of patients show the clinical triad at disease onset (4). That is why SS may be underdiagnosed.…”
Section: N Case Reportmentioning
confidence: 99%
“…1,2 The clinical triad of subacute encephalopathy, BRAO, and sensorineural hearing loss is diagnostic for this syndrome. 3,4 Clinical course. Based on expert guidelines, the patient was treated with IV methylprednisolone (1 g/daily for 3 consecutive days), IV immunoglobulin (IVIg), and IV cyclophosphamide followed by an oral prednisone taper and plans for monthly IVIg and cyclophosphamide infusions.…”
Section: Sectionmentioning
confidence: 99%
“…7 The average age at onset is 31.6 years (range 20-40 years) and it affects woman disproprotionately. 3,7 In addition to encephalopathy, BRAOs, and hearing loss, common clinical manifestations include impaired cognition and memory, ataxia, dysarthria, vertigo, corticospinal tract dysfunction, and headache with migrainous features in approximately half of cases. There has been no evidence of hereditary transmission and the etiology is thought to be autoimmune.…”
Section: Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Headaches at the onset of disease presentation are common (approximately 80%). 2 Encephalopathy is the most common initial symptom.…”
mentioning
confidence: 99%